Keats and negative capability - Li, Ou (Continuum literary studies., 2009)
""Negative capability"", the term John Keats used only once in a letter to his brothers, is a well-known but surprisingly unexplored concept in literary criticism and aesthetics. This book is the first book-length study of this central concept in seventy years. As well as clarifying the meaning of the term and giving an anatomy of its key components, the book gives a full account of the history of this idea. It traces the narrative of how the phrase first became known and gradually gained currency, and explores its primary sources in earlier writers, principally Shakespeare and William Hazlit.